A new HLA‐B allele, B*49:34, sequenced in a Spanish individual. Issue 4 (April 2015) - Azcarate, M.; Santos, S.; Balas, A.; Eguizabal, C.; Vicário, J. L.
Abstract : HLA‐B*49:34 shows one nucleotide difference regarding B*49:01:01 at codon 66 (ATC>GTC, I66>V66).